Characterisation of the immune-related transcriptome in resected biliary tract cancers. (November 2017) - Ghidini, Michele; Cascione, Luciano; Carotenuto, Pietro; Lampis, Andrea; Trevisani, Francesco; Previdi, Maria Chiara; Hahne, Jens C.; Said-Huntingford, Ian; Raj, Maya; Zerbi, Alessandro; Mescoli, Claudia; Cillo, Umberto; et al.
Abstract: Although biliary tract cancers (BTCs) are known to have an inflammatory component, a detailed characterisation of immune-related transcripts has never been performed. In these studies, nCounter PanCancer Immune Profiling Panel was used to assess the expression of 770 immune-related transcripts in the tumour tissues (TTs) and matched adjacent tissues (ATs) of resected BTCs. Cox regression analysis and Kaplan–Meier methods were used to correlate findings with relapse-free survival (RFS). The first analysis in the TT and AT of an exploratory set (n = 22) showed deregulation of 39 transcripts associated with T-cell activation. Risk of recurrence was associated with a greater number of genes deregulated in AT in comparison to TT. Analysis in the whole set (n = 53) showed a correlation between AT cytotoxic T-lymphocyte antigen-4 (CTLA4) expression and RFS, which maintained statistical significance at multivariate analysis. CTLA4 expression correlated with forkhead box P3 (FOXP3) expression, suggesting enrichment in T regulatory cells. CTLA4 is known to act by binding to the cluster of differentiation 80 (CD80). No association was seen between AT CD80 expression and RFS. However, CD80 expression differentiated prognosis in patients who received adjuvant chemotherapy. We showed that the immunomodulatory transcriptome is deregulated in resected BTCs. Our study includes a small number of patients and does not enable to draw definitive conclusions; however, it provides useful insights into potential transcripts that may deserve further investigation in larger cohorts of patients. Transcript Profiling: Nanostring data have been submitted to GEO repository: GSE90698 and GSE90699. Highlights: BTCs harbour a derangement of immune-related transcripts with an important role for the cytotoxic T-lymphocyte antigen-4 (CTLA4) axis. CTLA4 expression in the peritumoural areas correlates with outcome and represents a potential promising prognostic factor. Our data suggest that immunotherapy may have an impact in BTCs as a mean to re-address the host immune response to the tumour.